Predator Avoidance in the European Seabass After Recovery From Short-Term Hypoxia and Different CO2 Conditions - Steckbauer, Alexandra; Díaz-Gil, Carlos; Alós, Josep; Catalán, Ignacio A.; Duarte, Carlos M. (Frontiers in Marine Science, 2018)
Short-term hypoxia that lasts just a few days or even hours is a major threat for the marine ecosystems. The single effect of the human-induced levels of hypoxia and other anthropogenic impacts such as elevated pCO2 can reduce the ability of preys to detect their predators across taxa. Moreover, both processes, hypoxia and elevated pCO2, are expected to co-occur in certain habitats, but the synergic consequences of both processes and the ability of fish to recover remain unknown. To provide empirical evidence to this synergy, we experimentally evaluated the risk-taking behavior in juveniles of the European seabass (Dicentrachus labrax), an important commercial fisheries species after recovering from short-term hypoxia and different pH scenarios. The behavior of seabass juveniles was monitored in an experimental arena before and after the exposure to a simulated predator and contrasted to control fish (BACI design) (current levels of hypoxia and elevated pCO2) using a mechanistic function-valued modeling trait approach. Results revealed that fish recovering from elevated pCO2, alone or combined with hypoxia, presented less avoidance behavior in failing to seek refuge when a simulated predator was present in the arena compared to those exposed to control pCO2 levels. Our results show that recovery from short-term exposure to acidification and hypoxia was not synergistic and suggest that recovery from acidification takes longer than from short-term hypoxia treatment through a potential effect on the sensorial and hence behavioral capacities of fish.